f(x) = sin(log(x)) and y = f((2x +3) / (3 - 2x))
I will assume that the base of log(x) is e and I will use ln(x) in my answer.
y is a composition of functions, so let's add some notation to make this more obvious.
Let:
p(x) = sin(x)
q(x)= ln(x)
u(x) = 2x + 3
v(x) = 3- 2x
then:
y(x) = p(q((u(x))/(v(x))))
We could attack this directly, but a property of logs can simplify it a bit:
q((u(x))/(v(x))) = ln((u(x))/(v(x))) = ln(u(x)) - ln(v(x))
u'(x) = 2
v'(x) = -2
q'(x) = (u'(x))/(u(x)) - (v'(x))/(v(x)) = 2/(2x + 3) - (-2)/(3- 2x)
= 2/(2x + 3) - 2/(2x- 3) = (4x - 6 -(4x + 6))/(4x^2 - 9)
= -(12)/(4x^2 - 9)
Applying the Chain Rule to y(x):
y'(x) = p'(q(x)) * q'(x)
p'(x) = cos(x)
so:
y'(x) = cos(ln((2x + 3)/(3- 2x))) * (-(12)/(4x^2 - 9))
= -(12*cos(ln((2x + 3)/(3- 2x))))/(4x^2 - 9)
SEE: https://www.khanacademy.org/math/ap-calculus-ab/ab-derivatives-advanced/ab-diff-log/v/chain-rule-with-triple-composition